The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12985-018-1113-5
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequences of Aeromonas and Pseudomonas phages as a supportive tool for development of antibacterial treatment in aquaculture

Abstract: BackgroundAquaculture is the fastest growing sector of food production worldwide. However, one of the major reasons limiting its effectiveness are infectious diseases among aquatic organisms resulting in vast economic losses. Fighting such infections with chemotherapy is normally used as a rapid and effective treatment. The rise of antibiotic resistance, however, is limiting the efficacy of antibiotics and creates environmental and human safety concerns due to their massive application in the aquatic environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…These bacteria are usually resistant to first and second line antibiotic therapy involving beta-lactam drugs and third generation cephalosporins via mechanisms such as resistance genes and biofilm formation (Janda and Abbott, 2010). Bacteriophages, which have been suggested as an alternative to antibiotics, have been isolated against environmental and fish pathogen strains of A. hydrophila (Chow and Rouf, 1983;Merino et al, 1990a,b;Gibb and Edgell, 2007;Shen et al, 2012;Jun et al, 2013;Anand et al, 2016;Wang et al, 2016;Le et al, 2018;Yuan et al, 2018;Bai et al, 2019;Cao et al, 2019;Kazimierczak et al, 2019). The host range of these bacteriophages, however, was not reported to extend to clinical strains.…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria are usually resistant to first and second line antibiotic therapy involving beta-lactam drugs and third generation cephalosporins via mechanisms such as resistance genes and biofilm formation (Janda and Abbott, 2010). Bacteriophages, which have been suggested as an alternative to antibiotics, have been isolated against environmental and fish pathogen strains of A. hydrophila (Chow and Rouf, 1983;Merino et al, 1990a,b;Gibb and Edgell, 2007;Shen et al, 2012;Jun et al, 2013;Anand et al, 2016;Wang et al, 2016;Le et al, 2018;Yuan et al, 2018;Bai et al, 2019;Cao et al, 2019;Kazimierczak et al, 2019). The host range of these bacteriophages, however, was not reported to extend to clinical strains.…”
Section: Discussionmentioning
confidence: 99%
“…As a phage therapy Le et al (2018) demonstrated that phages (Φ2 and Φ5) are considered as potential biocontrol agents to combat A. hydrophila infections in fish farms. In the same direction, Kazimierczak et al (2019) reported that, 6 new isolated phages could be used as a therapeutic cocktail giving the infected of 41% of the Aeromonas pathogenic environmental isolates. In this study, only 1.38 log CFU/g (P< 0.01) E. coli W102 viable count reduction was found with phage ΦECP8 treatment while 1.68 log CFU/g (P< 0.01) with phage ΦECP9 on tomato slices 30min of application at room temperature.…”
Section: Application Of Bacteriophages In Artificially Contaminated Fmentioning
confidence: 95%
“…Therefore, there are various approaches to define a phage life cycle [6,7]. It often starts with a search of reference sequences in Basic Local Alignment Search Tool (BLAST) and both automatic and manual annotation of genomes (e.g.in DNAMaster, University of Pittsburgh).…”
Section: Introductionmentioning
confidence: 99%